Social carrying capacity of ecotourism National Park Kuala Tahan - Ismail, Mohd Muzzammil; Jaafar, Mastura; Mohamad, Diana; Paijo, Mohd Amirul Nizam (2016)
Increasing recreational activities in National Park potentially affect the recreational quality. Carrying capacities for protected area such as National Park are highly essential factor for tourism management.The use of carrying capacity as predominant method synthetically presented in this study is focused on National Park Kuala Tahan, Pahang (NPKT).This study explores the concept of social carrying capacity (SCC) where concentration on the factors of individuals which park visitors becomes uncomfortable - satisfaction perception. For the SCC, 300 interviews were conducted at the study area exploring social attributes of tourism development and collected data subjected to a series of descriptive analysis methods.Output from factor analysis and mean scores confirmed that the ecotourism potentially provides a sustainable approach to tourism development in Malaysia. This study identifies the positives and negatives social effects of ecotourism development in NPKT from the perspectives of tourist’s satisfaction.